The importance of an asymmetric distribution of acidic lipids for synaptotagmin 1 function as a Ca2+ sensor - Lai, Ying; Shin, Yeon-Kyun (PORTLAND PRESS LTD, 2012)
Syt1 (synaptotagmin 1) is a major Ca2+ sensor for synaptic vesicle fusion. Although. Syt1 is known to bind, to SNARE (soluble N-ethylmaleimide-sensitive fusion protein-attachment protein receptor) complexes and to the membrane, the mechanism by which Syt1 regulates vesicle fusion is controversial. In the present study we used in vitro lipid-mixing assays to investigate the Ca2+-dependent Syt1 function in proteoliposome fusion. To study the role of acidic lipids, the concentration of negatively charged DOPS (1,2-dioleoyl-sn-glycero-3-phospho-L-serine) in the vesicle was varied. Syt1 stimulated lipid mixing by 3-10-fold without Ca2+. However, with Ca2+ there was an additional 2-5-fold enhancement. This Ca2+-dependent stimulation was observed only when there was excess PS (phosphatidylserine) on the t-SNARE (target SNARE) side. If there was equal or more PS on the v-SNARE (vesicule SNARE) side the Ca2+ dependent stimulation was not observed. We found that Ca2+ at a concentration between 10 and 50 mu M was sufficient to give rise to the maximal enhancement. The single-vesicle-fusion assay indicates that the Ca2+-dependent enhancement was mainly on docking, whereas its effect on lipid mixing was small. Thus for Syt1 to function as a Ca2+ sensor, a charge asymmetry appears to be important and this may play a role in steering Syt1 to productively trans bind to the plasma membrane.
Keywords: SYNAPTIC SNARE COMPLEX; MEMBRANE-FUSION; 3-DIMENSIONAL STRUCTURE; SINGLE-MOLECULE; I FUNCTIONS; CALCIUM; BINDING; MECHANISM; EXOCYTOSIS; AFFINITY